The nexus of public debt and economic growth in Ethiopia: Is it symmetric? - Chala Amante Abate (Cogent Economics & Finance, 2023)
AbstractThis study examines the nature of relationship between public debt and economic growth of Ethiopia. To this end, a time series data was collected over the period 1982–2018. Nonlinear ARDL and multiple thresholds nonlinear ARDL models were used to uncover whether the relationship between debt and economic growth of Ethiopia is asymmetric. Instrumental variable regression model with a quadratic specification was used to test threshold effect of debt. The results reveal there are evidences that support the existence of asymmetric relationship between the indicated variables. Accordingly, it was found that a major positive shock in debt is favorable to economic growth while the effect of a minor and negative shock to debt is unfavorable. The results further reveals that there is a threshold effect of debt such that it is beneficial to economic growth of Ethiopia when it is well below 66.75% of GDP or 36.27% of GNI. Above these threshold levels, debt incurred deteriorates economic growth of the country. The study recommends that government of Ethiopia should create conducive environment that helps to secure more debts from potential creditors and at the same time, keep the annual debt well below 66.75% of GDP and 36.27%.